2021
DOI: 10.1007/s00228-021-03134-9
|View full text |Cite
|
Sign up to set email alerts
|

A patient-centred web-based adverse drug reaction reporting system identifies not yet labelled potential safety issues

Abstract: Purpose Reporting of adverse drug reactions (ADRs) by patients is essential for a comprehensive risk–benefit evaluation of drugs after marketing, but only few data are available regarding patient-centred web-based ADR reporting systems. Hence, we aimed to analyze ADRs reported by patients with a particular emphasis on novel drugs and serious ADRs not yet labelled in the respective summary of product characteristics (SPC). Methods All ADR reports received b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…It is well‐known that women report more side effects. 30 , 31 A multitude of potential reasons exist for this difference, for example a higher polypharmacy rate, reaching a higher age, different baseline characteristics and risks (e.g. longer QT interval, higher prevalence of depression), physiological differences that can lead to higher average drug exposures, receiving different care, a different perception of healthcare professionals, and a different attitude towards drugs in women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well‐known that women report more side effects. 30 , 31 A multitude of potential reasons exist for this difference, for example a higher polypharmacy rate, reaching a higher age, different baseline characteristics and risks (e.g. longer QT interval, higher prevalence of depression), physiological differences that can lead to higher average drug exposures, receiving different care, a different perception of healthcare professionals, and a different attitude towards drugs in women.…”
Section: Discussionmentioning
confidence: 99%
“…This higher number probably derived from the twice higher total number of drug reports in comparison to men. It is well‐known that women report more side effects 30,31 . A multitude of potential reasons exist for this difference, for example a higher polypharmacy rate, reaching a higher age, different baseline characteristics and risks (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…10 Consumers often detect AMEs before their healthcare professionals notice them 11 , and, where patient engagement is implemented, consumer self-report of AMEs alert regulators to new and previously unknown reactions prior to health professional reports. 12,13 In Australia, however, the number of reports to regulators from consumers is disproportionately low compared to those made by healthcare professionals and pharmaceutical manufacturers 14 , partly because of consumers' limited awareness of the reporting system, and perceived absence of benefits of reporting. 15 The AME reporting system, developed by the medicine regulatory body, the Therapeutic Goods Administration (TGA), 14 has seen limited consumer uptake in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…Reports from patients are increasingly recognized as important sources of information about ADRs [ 14 ]. Previous studies have shown that patients are able to detect ADRs first [ 15 , 16 ], and that patient ADR reports alert regulatory authorities to new and previously unknown ADRs [ 17 ]. However, barriers such as lack of awareness of the importance of ADR reporting, difficulty using existing reporting systems due to complicated language and cumbersome interfaces, and negative reporting experiences mean that ADR reporting rates from patients remain very low [ 11 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%